2022
DOI: 10.1111/mms.12908
|View full text |Cite
|
Sign up to set email alerts
|

The effect of age, sex, and resource abundance on patterns of rake markings in resident killer whales (Orcinus orca)

Abstract: Fluctuations in aggressive behavior of group‐living species can reflect social conflict and competition for resources faced by individuals throughout their lifespan and can negatively impact survival and reproduction. In marine mammals, where social interactions are difficult to observe, tooth rake marks can be used as an indicator of received aggression. Using 38 years of photographic data, we quantified the occurrence of tooth rake marks on wild resident killer whales (Orcinus orca), examining the effects of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 89 publications
1
6
0
Order By: Relevance
“…Males exhibited the highest density of rakes and notches followed by unknown-sex dolphins and females, respectively. Such age-and sex-related patterns have previously been reported in other odontocete species, including killer whales (Grimes et al, 2022) and bottlenose dolphins (Lee et al, 2019;Marley et al, 2013). In addition, similar sex-related patterns have already been reported for IPHDs in Hong Kong and Taiwan (Wright et al, 2017).…”
Section: Age and Sexsupporting
confidence: 83%
See 1 more Smart Citation
“…Males exhibited the highest density of rakes and notches followed by unknown-sex dolphins and females, respectively. Such age-and sex-related patterns have previously been reported in other odontocete species, including killer whales (Grimes et al, 2022) and bottlenose dolphins (Lee et al, 2019;Marley et al, 2013). In addition, similar sex-related patterns have already been reported for IPHDs in Hong Kong and Taiwan (Wright et al, 2017).…”
Section: Age and Sexsupporting
confidence: 83%
“…Regarding prey availability, unexpectedly, Grimes et al (2022) reported an increase in rake density in killer whales as the abundance of their primary food resource increased. In addition, since dolphins hunt for mobile prey that is typically swallowed quickly and whole, they are not expected to compete for nor to share food (Mann & Sargeant, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, compensatory epidermal hyperplasia in response to the superficial lesion may facilitate virus replication. If either of these mechanisms are valid, the lower point prevalence in older females could be associated with older Southern Resident killer whale females having lower density of rake marks than other female age classes [ 56 ]. The rake-associated stage-class hypothesis, however, is not substantiated for calves.…”
Section: Discussionmentioning
confidence: 99%
“…The rake-associated stage-class hypothesis, however, is not substantiated for calves. Female Southern Resident killer whale calves experienced significantly higher rake density than all other female age categories [ 56 ] and male calves and male juveniles exhibited over twice the rake density of subadults and three times that of adult males [ 56 ]. While Geraci et al [ 93 ] suggest black pinpoint, grey and other lesions in dolphins are all progressions of poxvirus infection, currently, there is insufficient data to infer an etiology for these cutaneous lesions in Southern Resident killer whales.…”
Section: Discussionmentioning
confidence: 99%
“…During serious fighting, an attack is countered by a defense and if the combatants are equally matched in skill, few, if any, attacks reach their target (Geist, 1978), so much so, that the seeming rarity of injury often leads to serious fights being labeled as "ritualized" contests (Archer and Huntingford, 1994). However, the presence of combat-induced injuries has likely been underestimated (e.g., Geist, 1986;Huntingford and Turner, 1987;Ham et al, 2021;Grimes et al, 2022), and detailed analyses of actual combat reveals that when the opponent's defenses are breached, a combatant will not hesitate to deliver a potentially injurious attack (Geist, 1965, Geist, 1967Geist, 1971;Pellis et al, 2013). Moreover, if the recipient of an attack successfully wards off the offensive maneuver, it can deliver an offensive attack of its own.…”
Section: Cooperationmentioning
confidence: 99%